Antiretroviral therapy-induced paradoxical worsening of previously healed Mycobacterium haemophilum cutaneous lesions in advanced HIV infection - Eyer-Silva, Walter de Araujo; Almeida, Marina Rodrigues de; Martins, Carlos José; Basílio-de-Oliveira, Rodrigo Panno; Araujo, Luciana Ferreira de; Basílio-de-Oliveira, Carlos Alberto; Azevedo, Marcelo Costa Velho Mendes de; Pinto, Jorge Francisco da Cunha; Vasconcellos, Sidra Ezidio Gonçalves; Rodrigues-dos-Santos, Ícaro; MagdinierGomes, Harrison; Suffys, Philip Noel (Revista do Instituto de Medicina Tropical de São Paulo, 2019)
Mycobacterium haemophilum is a nontuberculous mycobacterium that causes localized or disseminated disease, mainly in immunocompromised hosts. We report the case of a 35-year-old HIV-infected woman who presented with several enlarging cutaneous lesions over the arms and legs. Histopathological examination revealed the diagnosis of a cutaneous mycobacterial disease. Mycobacterial analyses unveiled M. haemophilum infection. Six months after completion of a successful antimycobacterial treatment, she developed an immune reconstitution inflammatory syndrome (IRIS). This paradoxical relapse presented as tenderness, redness and swelling at the precise sites of the healed lesions and took place in the setting of significant recovery of the CD4 cell count (from 05 to 318 cells/mm 3 ). Microbiological analyses of these worsening lesions were negative, and they spontaneously remitted without the initiation of a novel antimycobacterial treatment cycle. M. haemophilum infection should always be considered as a cause of skin lesions in immunocompromised subjects. Physicians should be aware of the possibility of IRIS as a complication of successful antiretroviral therapy in HIV-infected patients with M. haemophilum infection.